Polymorphism of stearoyl-CoA desaturase (SCD1) gene in Indonesian local cattle - Hilmia, N.; Noor, R. R.; Sumantri, C.; Gurnadi, R. E.; Priyanto, R. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
Stearoyl-Coa desaturase (SCD1) gene is one of genes that involves in converting saturated fatty acids to unsaturated fatty acids. SNP at exon 5 in SCD1 gene that changes amino acid valine to alanine (V293A) has an influence to meat fatty acid composition. The aim of this research was to analyze SCD1 gene polymorphisms based on SNP V293A at exon 5 of three Indonesian local cattle. The identification of SCD1 gene polymorphisms was done by using 98, 20 and 7 DNA sample from Ciamis, Bali/Banteng, and Ongole Grade (PO) cattle, respectively. PCR_RFLP method with AciI enzim was carried out to identify SNP Val293Ala. Allelic frequencies and heterozygosity value were analyzed by using POPGENE32. The result showed that SCD1 gene at Ciamis local cattle and PO cattle were polymorphic. Their frequencies were 74.5% and 71.4% for T and 25.5% and 28.6% for C, respectively. There were three genotypes on Ciamis local cattle i.e TT, CT and CC with their frequencies were 52%, 44.9% and 3.10%, respectively. There were two genotypes on PO cattle i.e TT and CT with their frequencies were 42.9% and 57.1%, respectively. Meanwhile, SCD1 gene in Bali cattle was monomorphic. Heterozygosity value of SCD1 gene in Ciamis and PO cattle were 0.38 and 0.44, respectively. Their heterozigosities were categorized as medium.